The Level of Clinical Improvement in Sexually ID Abused Children Admitted to an Inpatient Child and Adolescent Mental Health Unit - Burcu Serim Demirgoren; Taner Guvenir; Oğuzhan Şimşek; Bahar Şen (Galenos Publishing House, 2020)
INTRODUCTION: Child sexual abuse is a major psychosocial problem, often leading to lifelong consequences and impairments for the victims. The association between child abuse and psychiatric diagnosis has been shown via cross-sectional and longitudinal studies. The aim of this study was to investigate the measured improvement in patients who had been diagnosed with CSA and who received treatment in a generic inpatient child and adolescent mental health unit. METHODS: The study sample included all of the 43 children and adolescents, aged 8-18 years, who were treated in the inpatient unit from 2005-2018 for exposure to sexual abuse. Data, including sociodemographic features, individual and familial risks, Children's Global Assessment Scale scores, and the Turkish version of Health of the Nation Outcome Scales - Children and Adolescents scores (HoNOSCA-TR), all of which were routinely calculated at admission and discharge, were collected retrospectively from the hospital's records. RESULTS: Results demonstrated that the average duration of stay at the unit was 85.74+-30.54 days. General functionality measured by the Children's Global Assessment Scale significantly increased from admission to discharge following psychiatric inpatient treatment (p<0.05). Moreover, there was also significant improvement in sexually abused children and adolescents as indicated with all of the HoNOSCA-TR subscales (p<0.05). DISCUSSION AND CONCLUSION: Our study demonstrates that sexually abused young people benefit from inpatient treatment and that milieu therapy, which facilitates positive and reparative social interactions with peers and members of the therapeutic team during daily activities and therapeutic interventions, is a primary contributor to sexually abused young patients successfully managing to improve their functioning.